The effects of urbanization on air pollution based on a spatial perspective: Evidence from China - Li Zhang; Shibing You; Miao Zhang; Shiwen Zhang; Shuaixiang Yi; Baokang Zhou (Frontiers in Environmental Science, 2022)
The severity of haze pollution has increased along with the growth of the economy and urbanization. Studying the relationship between urbanization and environmental pollution is extremely important from a practical standpoint in the context of encouraging new urbanization development in China. In this paper, we explore the impact mechanism of urbanization on air pollution, using a spatial Durbin model (SDM) build on panel data of 277 cities from 2010 to 2019. The findings demonstrate that urbanization significantly inhibits haze pollution across the country, with energy consumption structure and industrial structure upgrading acting as mediating factors. Moreover, economic growth, population aggregation, and openness to foreign investment aggravate pollution, whereas transportation facilities, urban vegetation areas, and wind speed reduce air pollution. Furthermore, foreign direct investment increases pollution nationwide while alleviating haze pollution in the eastern region. According to analysis of regional heterogeneity, there is a nonlinear relationship between urbanization and pollution in the central and western cities, while development and pollution in the eastern cities show a tendency to decouple. On this basis, this paper puts forward some policy recommendations to attenuate the vicious linkage between urbanization and pollution in order to promote high-quality urbanization development.